The α9α10 acetylcholine receptor: A non-neuronal nicotinic receptor - Ana Belén Elgoyhen (Elsevier, 2023)
Within the superfamily of pentameric ligand-gated ion channels, cholinergic nicotinic receptors (nAChRs) were classically identified to mediate synaptic transmission in the nervous system and the neuromuscular junction. The α9 and α10 nAChR subunits were the last ones to be identified. Surprisingly, they do not fall into the dichotomic neuronal/muscle classification of nAChRs. They assemble into heteropentamers with a well-established function as canonical ion channels in inner ear hair cells, where they mediate central nervous system control of auditory and vestibular sensory processing. The present review includes expression, pharmacological, structure-function, molecular evolution and pathophysiological studies, that define receptors composed from α9 and α10 subunits as distant and distinct members within the nAChR family. Thus, although α9 and α10 were initially included within the neuronal subdivision of nAChR subunits, they form a distinct clade within the phylogeny of nAChRs. Following the classification of nAChR subunits based on their main synaptic site of action, α9 and α10 should receive a name in their own right.